The Effect of Rice Husk and Saw Dusk Filler on Mechanical Property of Bio Composite from Sago Starch - Rozanna Dewi; Novi Sylvia; M Riza (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
Some materials derived from plants can be used as a source of biodegradable thermoplastic materials such as rice, potatoes, corn, sweet potatoes, sago, etc. In this research, thermoplastic sago starch (TPS) with a mixture of two types of fillers was synthesized to become environmentally friendly composites that can be naturally degraded in a relatively short time compared to other conventional plastics which decompose in decades, hence can contribute to environmental conservation efforts. Increasing the strength of bio composite through the presence of fillers will expand its application such as for household application. Sago is available in large quantities in Indonesia and needs to be utilized optimally to increase its added value. TPS is synthesized using sorbitol as a plasticizer so that it becomes a starch paste. Composites are moulded by means of compression moulding using TPS and cellulose as a filler and Polypropylene (PP). The fillers used were sawdust and rice husk with several variations to obtain optimal combination, to improve the mechanical performance of the composites. For rice husk fibre, the highest tensile strength value 13.82 MPa, found at 40% fibre with ratio of TPS: PP 1: 0.5, and the highest elongation value was 16.47% at 40% fibre at ratio of TPS : PP 1: 0.5. For Sawdust fibre, the highest tensile strength value 11.08 MPa, obtained at 20% fibre at ratio of TPS : PP 1 : 1, and the highest elongation value was 18.57% at 20% fibre with ratio of TPS : PP 1 : 1. Type of filler has different effect on the tensile strength and elongation of the bio composite,